RANCANG BANGUN SISTEM PENDUKUNG KEPUTUSAN PENGELOLAAN DANA BOS DENGAN METODE ANALYTICAL HIERARKHI PROCESS (AHP) - Purnama, Reza Rangga (Jurusan Informatika Universitas Tanjungpura, 2015)
Abstract - BOS (School Operational Assistance) is program to help provide funding for the costs of non-personnel basic education unit as the implementation of compulsory education are distributed to educational institutions, especially for elementary school through both public and private junior high school that has been designated by the Department of Education are distributed each particular period. Funds were caused problems for management, where the funds should be targeted. The objective to be achieved through this thesis is to design Decision Support System Management BOS with AHP-based desktop to the use of the funds targeted as needed. The method used in the design of this system is using hierarchies Analytical Process (AHP). AHP is a process that begins with structuring condition / complex problem into its components in the hierarchy. There are 27 sub-criteria that are part of the seven criteria: graduation competency development, development of content standards, standards development process, development of education and educational staff, school facilities and infrastructure development, development of management standards, development assessment system implementation. Every teacher and Principal provides an assessment on any existing criteria based on the level of importance. The application will compare the assessment has been done by all teachers and principals and provide an alternative decision. From the results of these calculations, the Principal may give weight to the cost required. The results showed that the design and testing of this application can be used for management and BOS.